Research on Artificial Intelligence. A proposal for bibliometric analysis in Spain and LATAM - Antona-Jimeno, Tamara; Vicent-Ibáñez, Mireya; Segado-Boj, Francisco (Revista General de Información y Documentación, 2024)
This research uses bibliometric analysis to assess whether Artificial Intelligence (AI) is a mature research field. Based on 609 articles from the Web of Science database, the results show that AI research in Spain is mature, with a focus on journalism and technology, and features established reference groups and well-defined theoretical foundations. In LATAM, the field is less developed and more fragmented. Trends in both contexts are centred on journalism, disinformation, and social media.